Exploring Metacognitive Strategies in Reading Academic Texts Among More and Less Proficient EFL University Students - Ali Roohani; Raheleh Sabzeali,; Azizullah Mirzaei (Journal of Modern Research in English Language Studies)
Research has showed a positive relationship between metacognitive knowledge and success in reading comprehension. Thus, it is important to be aware of metacognitive strategy use in reading comprehension. This study was intended to explore metacognitive strategies in reading academic texts among more and less proficient English university student readers. To this end, 75 English as a foreign language (EFL) students (including 45 more proficient and 30 less proficient students), who were selected nonrandomly from two  universities, participated in this mixed-methods study. To collect data, the Survey of Reading Strategies and the Test of English as Foreign Language were administered to them. Also, to elicit how they utilize the metacognitive strategies, five more proficient and five less proficient EFL readers were asked to undertake think-aloud tasks. Results of quantitative (t-tests) and qualitative data analysis showed that there were significant differences between the metacognitive strategies used by more and less proficient readers. More proficient readers reported using the strategies at a high frequency level overall, but less proficient readers reported using them at a moderate frequency level. More proficient readers preferred to use problem-solving strategies followed by global strategies, whereas less proficient ones preferred to use problem solving strategies followed by support strategies. In addition, the results of think-aloud indicated that the more and less proficient readers’ methods of employing metacognitive strategies differed, to some extent, from each other in quality of use. The findings provide implications for low proficiency EFL readers who intend to improve their reading comprehension and learning autonomy.